2014
DOI: 10.1111/1750-3841.12717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rigor Status during High‐Pressure Processing on the Physical Qualities of Farm‐Raised Abalone (Haliotis rufescens)

Abstract: High-pressure processing (HPP) is used to increase meat safety and shelf-life, with conflicting quality effects depending on rigor status during HPP. In the seafood industry, HPP is used to shuck and pasteurize oysters, but its use on abalones has only been minimally evaluated and the effect of rigor status during HPP on abalone quality has not been reported. Farm-raised abalones (Haliotis rufescens) were divided into 12 HPP treatments and 1 unprocessed control treatment. Treatments were processed pre-rigor or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…HP-treatment confirmed a significant change in the quality indices (microstructure, color, texture, and biochemical indices) of abalone muscle at pressure treatment of 500 MPa/8 min or 550 MPa/3-5 min while compared with raw abalone meat (Briones-Labarca et al, 2012). Conversely, pressurization (100-300 MPa/1-3 min) of fish resulted in a significant toughening to pre-rigor fish meat, while the texture of post-rigor processed fish was not significantly affected (Hughes et al, 2015). The protein structures, in particular, secondary, tertiary, and quaternary have been affected by the pressure treatment.…”
mentioning
confidence: 67%
“…HP-treatment confirmed a significant change in the quality indices (microstructure, color, texture, and biochemical indices) of abalone muscle at pressure treatment of 500 MPa/8 min or 550 MPa/3-5 min while compared with raw abalone meat (Briones-Labarca et al, 2012). Conversely, pressurization (100-300 MPa/1-3 min) of fish resulted in a significant toughening to pre-rigor fish meat, while the texture of post-rigor processed fish was not significantly affected (Hughes et al, 2015). The protein structures, in particular, secondary, tertiary, and quaternary have been affected by the pressure treatment.…”
mentioning
confidence: 67%
“…Studies also explored the advantages of HPP for shelf‐life extension (Gou, Lee, & Ahn, 2010) and inactivation of biogenic amines (Gou, Xu, Choi, Lee, & Ahn, 2010) in seafood. During the last decade, studies have determined the HPP‐induced physicochemical changes in Atlantic salmon muscle (Ojagh, Núñez‐Flores, López‐Caballero, Montero, & Gómez‐Guillén, 2011), herring ( Clupea harengus ), and haddock ( Melanogrammus aeglefinus ) (Karim et al., 2011), horse mackerel ( Trachurus trachurus ) (Pazos, Méndez, Vázquez, & Aubourg, 2015; Torres, Saraiva, Guerra‐Rodríguez, Aubourg, & Vázquez, 2014), sea bass ( Dicentrarchus labrax ) (Teixeira et al., 2014), Atlantic mackerel (Fidalgo, Saraiva, Aubourg, Vázquez, & Torres, 2014; Pazos, Méndez, Fidalgo, et al., 2015), hilsa ( Tenualosa ilisha ) (Chouhan, Kaur, & Rao, 2015), mild‐smoked rainbow trout ( Oncorhynchus mykiss ) and fresh European catfish ( Silurus glanis ) (Mengden, Röhner, Sudhaus, & Klein, 2015), and farm‐raised abalone ( Haliotis rufescens ) (Hughes, Greenberg, Yang, & Skonberg, 2015). Good overviews of the earlier work were prepared by Truong, Buckow, Nguyen, and Stathopoulos (2016) and Oliveira et al.…”
Section: Resultsmentioning
confidence: 99%
“…The rigor status of abalones during processing has recently been reported to impact post-processing texture. Compared to unprocessed controls, the texture of pre-rigor processed (100 MPa and 300 MPa) abalone toughened, while texture of post-rigor processed abalone did not differ from unprocessed controls (Hughes et al, 2015). HPP has only recently been explored for shelf-life extension of abalone, with very high pressures (≥500 MPa) for 5-8 min extending refrigerated shelf-life of abalone to 60-65 days and low pressure (200 MPa) for a short processing time (3 min) extending shelf-life to only 10 days (Briones et al, 2010;Jo et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…The whiteness of abalone meat is positively associated with its value, which can promote trimming or chemical bleaching of the meat to improve color (Oakes and Ponte, 1996;Allen and others 2006;Brown and others 2008). The whitening effect of HPP on fish is well documented (Ohshima et al, 1993;Sequeria-Munoz et al, 2006;Yagiz et al, 2007;Yagiz et al, 2009;Erkan et al, 2010) however has been inconsistent for abalone with two studies reporting L values increased with pressures up to 300 MPa (Hughes et al, 2015) and up to 500 MPa (Jo et al, 2014). Another study reported no effect of pressure on L values at 550 MPa but a decrease at 500 MPa (Briones-Labarca et al, 2012).…”
Section: Colormentioning
confidence: 99%